(untitled) - Graham, Margaret B. W. (Cambridge, 1990)
Examines both the internal dynamic of the evolution of Alcoa and the impact of such external factors as the nation's changing R & D climate. The company's history reveals the special nature of process R & D as well as the problems it poses for research management.
Keywords: Ngành công nghiệp nhôm và thương mại,Aluminum industry and trade; Đổi mới công nghệ,Technological innovations; Hoa Kỳ,United States